Variations in Pod and Seed Traits of Dalbergia sissoo in Different Seed Sources from Himachal Pradesh, India - Dhiman, Meenakshi; Rana, Neerja; Kumar, Vinay (Indian Forester, 2020)
The evaluations of seed and pod parameters are important criteria for quality seedling production for out planting and to maintain the fertility of soil for longer time. The present study was conducted to elucidate the pattern of variation in pods, seed characteristics and germination behavior among Dalbergia sissoo seed sources to develop criteria for improvement of tree seedlings in future programmes. Five seed sources from Himachal Pradesh (Solan, Hamirpur, Kangra, Bilaspur and Una) were selected to represent widely divergent areas. All the characterstics of pod (pod weight, length and width), seed (No. of seeds, length, width, thickness, weight and volume) and germination parameters (germination percentage, germination value, germination period) were observed for variation in different seed sources. Among the selected five seed sources, Bilaspur from Himachal Pradesh exhibited highest pod characters viz., 1000 pod weight (52.86 g), pod length (8.30 cm), pod width (1.15 cm), number of seeds/pod (2.33), seed length (8.37mm), seed width (4.55mm), seed weight (20.46g), seed thickness (1.07mm), seed volume (0.99cc), 85.94% germination, germination value 266.04, germination energy index 9.64, vigour index of 499.26 and showed least germination period of 6.66 days. Hence Bilaspur seed source have best pod and seed source and can be used for quality seedling production with better germination.